ANALISIS YURIDIS KONTRAK KERJA KONSTRUKSI PEMBANGUNAN GEDUNG SERBAGUNA DAN MASJID AT-TAWAZUN DI DESA SUKAASIH KECAMATAN SUKATANI KABUPATEN BEKASI - Firdaus Addar; Indah Kusuma Wardhani (Fakultas Hukum Universitas Borobudur, 2023)
The development of the construction services industry in Indonesia is always increasing, but problems still often occur related to construction work contracts, such as the substance of construction work contracts having multiple interpretations and the unequal position of the parties in carrying out their rights and obligations. Therefore, this research analyzes the Construction Work Contract for the Construction of the Multi-Purpose Building and the At-Tawazun Mosque, and discusses the process of making it, the rights and obligations of the parties, and the responsibilities of service users and service providers in the event of default. The methods used in this research are normative juridical and empirical juridical. The process of making a construction work contract can be divided into two stages, namely pre-contractual and contractual. Construction work contracts regulate the rights and obligations of the parties in accordance with the provisions of Article 47 paragraph (1), Article 54 and Article 55 of Law Number 2 of 2017 concerning Construction Services. The responsibility of the service provider in the event of default has also been regulated in Article 11, but the responsibility of the service user has not been regulated in the construction work contract. Thus, if the service user defaults, the service provider can file a breach of contract lawsuit based on Article 1243 of the Civil Code jo. Article 55 paragraph (2) Law Number 2 of 2017 concerning Construction Services.